Females and Footnotes: Excavating the Genre of Eighteenth-Century Women’s Scholarly Verse - Ruth Knezevich (ABO : Interactive Journal for Women in the Arts 1640-1830, 2016)
Throughout the eighteenth century, the genre of women’s poetry heavily annotated with editorializing commentary (a genre I term “scholarly verse”) became increasingly prevalent. Such poetry presents an ironic reversal of conventions of gender and authority by incorporating the literal margins of the page: the female voice commands the majority of the page, while the masculine voice of empiricism, authority, and scholarly reason is pushed to the margins. This essay offers a distant reading of the range of annotations women poets provided, in order to begin new conversations about the ways women’s poetry served as a site of and structure for intellectual exploration in the eighteenth century.